Kinetic coherence underlies the dynamics of disordered proteins. Issue 57 (10th November 2021) - Tenenbaum, Alexander
Abstract : In the phase space of a globular or intrinsically disordered protein, the momenta's dynamics is less chaotic than the coordinates' dynamics. When a protein is denaturated, a gain in kinetic coherence accompanies the loss of structural coherence. Abstract : The dynamics of two proteins of similar size, the globular lysozyme and the intrinsically disordered Huntingtin interacting protein, has been simulated in three states resembling a globule, a pre-molten globule, and a molten globule. A coherence time τ has been defined, measuring the delay in the display of a stochastic behaviour after a perturbation of the system. This time has been computed for two sets of collective variables: the projection of the phase point onto the positions and momenta subspaces ( τ r and τ p ), and the principal components (PCs) of positions q and momenta π produced by a covariance analysis in these subspaces ( τ q and τ π ). In all states τ p ≈ 3.5 τ r, and τ π ≈ 3.5 τ q . The coherence times of individual PCs, τ ( l )q and τ ( l )π, have also been computed, and τ ( l )π > τ ( l )q in all states. The prevalence of τ p over τ r, or of τ π over τ q, drives the dynamics of the protein over a time range of ≈1–2 ps; moreover, a hidden synchronism appears to raise the momenta subspace's coherence above that of its individual PCs. In the transition of lysozyme to the molten globule the τ ( l )q decrease but, unexpectedly, the τ ( l )π increase; after this transition τ p ≈ 5 τ r and τ π ≈ 5 τ q . A gain of kinetic coherence accompanies thus the loss of structural coherence caused by the denaturation of the protein in the transition from globule to molten globule. The increase of the τ ( l )π does not take place in the analogous transition of the Huntingtin protein. These results are compared with those of a similar analysis performed on three pseudo-proteins designed by scrambling the primary sequence of the Huntingtin interacting protein, and on two oligopeptides. The hidden synchronism appears to be a generic property of these polypeptides. The τ ( l )π spectrum is similar in denaturated and in intrinsically disordered biomolecules; but the gain of kinetic coherence as a result of denaturation seems to be a specific property of the biologically functional lysozyme.